Comparison of the effectiveness of online and face-to-face weight-loss interventions in the workplace: evidence from Malaysia - Roszanadia Rusali; Zahara Abdul Manaf; Suzana Shahar; Fatin Hanani Mazri; Norhayati Ibrahim; Arimi Fitri Mat Ludin; Devinder Kaur Ajit Singh; Nazlena Mohamad Ali (Penerbit Universiti Kebangsaan Malaysia, 2018)
A structured weight management programme at a workplace may help in reducing the prevalence of overweight and obesity. Therefore, this intervention study was to determine the effectiveness of weight loss programmes including face-to-face, online and control group at workplace among employees who are overweight and obese. A total of 108 overweight and obese adults were recruited and randomly divided into three groups (face-to-face group (FT), n=38; online group (OG), n=31; control group (CG), n=39). In the FT group, the participants took part in health talks, interactive activities and counselling; the OG group was given access to an online weight management program and the CG group was provided with educational booklets on weight loss. All information given was related to nutrition, physical activity and motivation to reduce weight. Body weight, body mass index (BMI), waist circumference (WC), body fat percentage, dietary intake, fasting lipid profile and glucose levels were assessed at baseline and 4 months. The FT group showed greater reduction in body weight (-5.80 kg) compared to OG (-1.12 kg) and CG (-1.82 kg). Significant interaction effects were found for BMI, WC, fasting serum triglycerides, HDL-cholesterol and total cholesterol/HDL-cholesterol ratio (all p<0.05), with the FT group showing the biggest improvements, compared to the other groups. The face-to-face weight management program offered in the workplace showed to be the most effective at improving anthropometric profile, fasting serum triglycerides, HDL-C, total cholesterol/HDL-C ratio, and dietary intake among overweight and obese employees.